Prevalence of SPOP and IDH Gene Mutations in Prostate Cancer in a Jordanian Population - Mohammed S. Alorjani (22282495) (2024)
Speckle-type POZ (SPOP) is described as an essential tumor suppressor factor in gastric cancer, colorectal cancer, and prostate cancer (PCa). SPOP gene mutations were reported in primary human PCa. Isocitrate dehydrogenase-1 (IDH1) oncogene mutations were detected in gliomas, acute myeloid leukemia, some benign and malignant cartilaginous tumors, and only 1% of PCa. This study aimed to investigate the prevalence of mutations of SPOP and IDH1 genes in PCa in the Jordanian population. One hundred formalin-fixed paraffin-embedded tissue samples were collected from patients diagnosed with prostate adenocarcinoma. The obtained specimens were subjected to genomic DNA extraction, PCR amplification, and direct sequencing of exons 4, 5, 6, and 7 of the SPOP gene and exon 6 of the IDH1 gene. SPOP gene mutations were found in 17% of PCa cases, while no mutation was detected in the screened exon 6 of the IDH1 gene. Clinicopathological data demonstrated a strong correlation between prostate-specific antigen (PSA) levels and both Gleason score (GS) and the International Society of Urological Pathology (ISUP) grade group (GG). There was no significant correlation between PSA levels and age (p= 0.816) nor there were significant associations for SPOP mutational status with age (p= 0.659), PSA levels (p= 0.395), GS (p= 0.259), and ISUP GG (p= 0.424) in the tested population. The study found a strong correlation between PSA levels and both GS and ISUP GG. It also identified a high frequency (17%) of SPOP gene mutations in Jordanian Arab PCa patients, mainly in exon 7. No IDH1 mutations were detected in exon 6. Other Information Published in: Biochemical Genetics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s10528-024-10974-4